The Spicy Science of Dendrimers in the Realm of Cancer Nanomedicine: A Report from the COST Action CA17140 Nano2Clinic - Sabrina Pricl (MDPI AG, 2023)
COST Action CA17140 Cancer Nanomedicine-from the bench to the bedside (Nano2Clinic,) is the first, pan-European interdisciplinary network of representatives from academic institutions and small and medium enterprises including clinical research organizations (CROs) devoted to the development of nanosystems carrying anticancer drugs from their initial design, preclinical testing of efficacy, pharmacokinetics and toxicity to the preparation of detailed protocols needed for the first phase of their clinical studies. By promoting scientific exchanges, technological implementation, and innovative solutions, the action aims at providing a timely instrument to rationalize and focus research efforts at the European level in dealing with the grand challenge of nanomedicine translation in cancer, one of the major and societal-burdening human pathologies. Within CA17140, dendrimers in all their forms (from covalent to self-assembling dendrons) play a vital role as powerful nanotheranostic agents in oncology; therefore, the purpose of this review work is to gather and summarize the major results in the field stemming from collaborative efforts in the framework of the European Nano2Clinic COST Action.